Information Security Analysis and Solution using LSB Steganography and AES Cryptographic Algorithm - Nurul Adha, Oktarini Saputri; Novita Epa, Sari (INTI International University, 2023)
The significance of information security analysis and solutions has been emphasized by earlier research in several application areas. As a result, information technology has advanced more, particularly in the areas of security and data secrecy. An essential component of data exchange is security and confidentiality. A message must first be hidden or encrypted in the picture media to ensure its security and confidentiality. Our research presents a method for this study, which involves hiding digital images with color at a depth of 24 bits. Through the development of a system to improve the security and confidentiality of data in the form of critical messages, this study seeks to provide senders with solutions. Images are encrypted using the least significant bit (LSB) steganography technique. The AES algorithm is the cryptographic technique used to lock or encrypt data. The LSB utilized in this work involves putting ciphertext bits into the image's color component pixel matrix's diagonals. In this work, the recovery elements of the modified LSB and AES algorithms were examined to conduct testing.